Comparison of Wound Healing Time in Circumcision Patients with the Finesealer Method and the Electrical Cauter Method - Siregar, Annisa Mutiara Naulita; Hamdani, Irfan (Buletin Farmatera, 2026)
Abstract: Circumcision is an operative action performed by cutting the prepuce to prevent infection in the penis and is considered a religious practice, especially in Islam. There are many modern circumcision methods, one of which is the fine sealer method and the electrical cauter method, with different processes and results. This study aims to determine the process of healing wounds after circumcision by comparing the results of circumcision in the fine sealer method and the electrical cauter method. This study uses an observational analytical research type with a case-control design. This study was conducted by comparing the circumcision results of the group of children who underwent circumcision with the fine sealer method and the group of children with the electrical cauter method. The number of subjects studied was 60 children, with 30 children in the fine sealer group and another 30 children in the electrical cauter group. Data analysis used the Kolmogorov-Smirnov normality test and the Mann-Whitney test as a comparative test. There was a significant difference in post-circumcision wound healing between the fine sealer and the electrical cauter with a significance value of 0.000 (p0.05) and there was a difference  in mean rank for the two methods with  the mean rank in the electrical cauter group  of 39.00 compared to  the  fine sealer  group of only 22.00. This study concludes that the fine sealer method shows a faster healing process than the electrical cauterisation method.